Adsorption Characteristics of Ethyl Paraben from Aqueous Solution Using Rice Husk Biochar. Issue 1 (September 2020) - Guo, Meng; Chen, Wenjing; Ru, Han; Yang, Lili; Zhang, Yu
Abstract: The rice husk was used as raw material to prepare the biochar adsorbent at 300°C, 400°C and 500°C, which were named BC300, BC400 and BC500. Ethyl paraben was subject to batch adsorption in aqueous medium by the prepared rice husk biochar. The results of adsorption experiments show that the preparation temperature of biochar significantly affects its adsorption effect on ethyl paraben. The adsorption capacity of ethyl paraben from three kinds of biochar was BC500 > BC400 > BC300. In addition, the initial concentration of ethyl paraben in waste water, the temperature and time of adsorption can also affect the adsorption effect. The reaction reached adsorption equilibrium after 270min. The results showed a theoretical basis for the removal of organic pollutants such as ethyl paraben.